PENINGKATAN PENGETAHUAN REMAJA TENTANG BAHAYA ROKOK ELEKTRONIK: Improving Adolescents Knowledge About the Harmful Effect of Electronic Cigarette - Desak Made Sintha Kurnia Dewi; Susy Katikana Sebayang; Septa Indra Puspikawati; Erni Astutik; Syifa'ul Lailiyah; Erlin Qur’atul Aini; Rizky Putri Hariyani (Lembaga Penelitian dan Terapan untuk Kesehatan Jiwa (Lenterakaji), 2020)
ABSTRACTThe popularity of e-cigarette (e-cig) is increasing among adolescents, as it is promoted as a safer cigarette and a tool that can help to quit smoking. The misleading security illusion of e-cig without adequate knowledge has created a new generation of tobacco industry customers. The aim is to improve adolescent knowledge about the harmful effects e-cig. Online socialization about the electronic cigarette traps were given to junior and senior high school students in two sub districts in Banyuwangi. Education was conducted in October 2020, attended by 107 students and 15 teachers.Three educational sessions for 20 minutes were conducted using presentation and short video. Pre and post tests were conducted to measure changes in adolescent knowledge. Participants were also asked to evaluate the benefits of these activities. Paired sample t test was used to analyze adolescents’ knowledge before and after socialization. Online socialization about the harmful effect of e-cig improved adolescent knowledge. The mean score improvement was 0.88 ± 1.499 (p = 0.0004). Around 72.1% of adolescents were willing to become agents of change or peer educators. About 84.4% and 88.3% participants agreed and strongly agreed that this socialization provided new information and understanding. Online socialization about the harmful effect of e-cig using short video and texts can improve adolescents' knowledge.Keywords: E-cigarette, Adolescents, Addiction, Tobacco Control. ABSTRAKRokok elektronik (e-cig) semakin populer khususnya di kalangan remaja karena dipromosikan sebagai rokok yang lebih aman dan alat bantu untuk berhenti merokok. Keamanan palsu (ilusif) yang diberikan e-cig tanpa diimbangi pengetahuan yang cukup menciptakan generasi pelanggan baru untuk industri tembakau. Tujuan dari studi ini adalah untuk meningkatkan pengetahuan remaja tentang bahaya rokok elektronik. Sosialisasi Jebakan Rokok Elektronik dilakukan secara daring pada pelajar SMP dan SMA di dua Kecamatan di Banyuwangi. Edukasi dilaksanakan pada Oktober 2020, diikuti oleh 107 siswa dan 15 guru. Tiga sesi edukasi selama 20 menit dilaksanakan menggunakan presentasi dan video pendek. Pre dan post-test digunakan untuk mengukur perubahan pengetahuan peserta. Peserta juga diminta untuk mengevaluasi manfaaat dari kegiatan ini. Paired sample t test digunakan untuk menganalisis pengetahuan remaja sebelum dan setelah sosialisasi. Sosialisasi secara daring tentang bahaya e-cig mampu meningkatkan pengetahuan remaja. Peningkatan skor rata rata sebesar 0.88±1.499 (p=0.0004). Sebanyak 72.1% remaja menyatakan kesediaannya menjadi agen perubahan atau peer educator. Sebanyak 84.4% dan 88.3% peserta setuju dan sangat setuju bahwa sosialisasi ini memberi informasi dan pemahaman baru. Sosialisasi daring tentang bahaya e-cig menggunakan video pendek dan text dapat meningkatkan pengetahuan remaja.Kata Kunci: Rokok Elektronik, Remaja, Kecanduan, Kontrol Tembakau.